School Gates are Re-Opened: The Lived Experiences of Kindergarten Teachers in the Post-Pandemic Era: The Lived Experiences of Kindergarten Teachers in the Post-Pandemic Era - Ronia, Dr. Cecilia; Buitizon, Starlene; Licayan, Felicity Duane; Bacus, Arvie; De Guzman, Mary Grace; Ramos, Rowena Imelda (12th International Scholars Conference 2025, 2026)
The reopening of schools after the COVID-19 pandemic introduced a transformative phase in education. This study explores the lived experiences of kindergarten teachers during the school years, 2022 - 2024, in Silang, Cavite, using a transcendental phenomenology approach. Using Moustakas' (1994) Transcendental Phenomenology Data Analysis Framework, the study examined the teachers navigating shifts in pedagogy, technology integration, and their relationships with pupils, parents, and colleagues during an educational era in the aftermath of the worldwide pandemic. Supported by Bronfenbrenner’s Ecological Theory, Community of Inquiry, and the Technology Integration Matrix, the study highlights the challenges and adaptations faced by teachers, including psychosomatic stress, technological innovation, and the rebuilding of social connections in a post-pandemic context. The findings provide valuable insights for teachers, administrators, and policymakers to enhance pedagogical practices, support networks, and resilience in early childhood education (ECE).